Efficacy and safety of nivolumab in the treatment of relapsed/refractory classical Hodgkin’s lymphoma: Pavlov First Saint Petersburg State Medical University experience - K. V. Lepik; N. V. Mikhailova; E. V. Kondakova; L. A. Tsvetkova; Yu. R. Zalyalov; E. S. Borzenkova; I. S. Moiseev; V. V. Baykov; B. A. Afanasyev (Онкогематология)
Background . Using modern first-line chemotherapy more than 80 % of patients with classical Hodgkin’s lymphoma can be cured, however, in 15–20 % of cases there is a relapsed/refractory disease. The use of nivolumab in international clinical practice has significantly improved treatment results of patients with relapsed/refractory classical Hodgkin’s lymphoma.Objective of this study is to evaluate the results of therapy with nivolumab in the сlinic of Pavlov First Saint Petersburg State Medical University.Materials and methods . The retrospective analysis included treatment results of 101 patients with relapsed/refractory classical Hodgkin’s lymphoma who received nivolumab in Raisa Gorbacheva Memorial Research Institute of Children Oncology, Hematology and Transplantation from February 2016 to August 2018. The group included 90 patients who received nivolumab as part of an named patient program. Therapy response was assessed using CT/PET-CT in accordance with LYRIC criteria for response assessment of malignant lymphomas to immunotherapy. Safety and tolerability were assessed by registering adverse events in accordance with NCI CTCAE version 4.03 criteria. Results . Median follow-up was 25 months. The response was registered in 64 % of patients: in 32 (31.6 %) – complete response and in 33 (32.7 %) – partial response. Stabilization and progression as the best response were registered in 5 (4.9 %) and 10 (9.8 %) patients, respectively. Indeterminate response was observed in 21 (20.6 %) patients. The 2-year overall survival was 96 %; the median of overall survival was not achieved. Progression-free survival (PFS) in studied patients was 40.6 %. The median of PFS was 17.9 months. There were no significant differences in PFS between patients with a partial and indeterminate response. Adverse events were reported in 87.1 % of patients. Severe adverse events (III–IV grade) occur in 18.8 % of patients.Conclusion . The results of a retrospective study of nivolumab therapy in Russian patients with relapsed/refractory classical Hodgkin’s lymphoma are consistent with published international data. Nivolumab demonstrates high efficacy as a monotherapy for relapsed/refractory classical Hodgkin’s lymphoma, regardless of previous therapy type and duration with well tolerance. Pseudo-progression phenomena during immunotherapy require revision of the traditional Hodgkin’s lymphoma therapy response criteria.